Gambaran Makroskopis Persembuhan Luka Mukosa Buccal Tikus Putih (Rattus norvegicus) Pascapemberian Policresulen - Tri Isyani Tunggadewi; Tony Wahyudi; Aisyah Alviatus Shofwan; Anggri Azhari Khoerunnisa; Huda Salahudin Darusman (ARSHI Veterinary Letters, 2020)
This study aimed to investigate the effect of policresulen treatment with various concentrations on the wound healing in buccal mucosa of white rats (Rattus norvegicus) through macroscopically observation. The number of 54 rats were divided into six treatment groups policresulen with concentration of 36%, 10%, 5%, 1%, 0.3% and one control group. The buccal mucosal injury was made with a 0.5 cm biopsy punch. The treatment of mucosal injury was conducted by dropped policresulen on the 2nd day until the 5th day after the injury. Macroscopic observation under a stereo micro-scope was conducted on the wound diameter, redness, swelling, and necrose. The results showed that wound healing was influenced significantly with concentration of the policresulen. The best healing was shown on lowest concentration marked which has lowest size of the wound diameter (0.50 ± 0.00 cm), the lowest tissue redness (0.00 ± 0.00), lowest final swelling at a concentration of 0.3%. Clinical evaluation of wound tissue necrose parameters which were seen to be most severe at 10% policresulen administration followed by 36% concentration and the least necrose shown on policresulen administration 0.3%. Therefore, based on macroscopic images with parameters of wound diameter, redness, swelling, and necrose suggested that policresulen used for wound healing process are at a concentration of 0.3%.